The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/microorganisms8040573
|View full text |Cite
|
Sign up to set email alerts
|

The Controversial Role of Human Gut Lachnospiraceae

Abstract: The complex polymicrobial composition of human gut microbiota plays a key role in health and disease. Lachnospiraceae belong to the core of gut microbiota, colonizing the intestinal lumen from birth and increasing, in terms of species richness and their relative abundances during the host’s life. Although, members of Lachnospiraceae are among the main producers of short-chain fatty acids, different taxa of Lachnospiraceae are also associated with different intra- and extraintestinal diseases. Their impact on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
715
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 962 publications
(863 citation statements)
references
References 204 publications
38
715
4
2
Order By: Relevance
“…Many Lachnospiraceae members have been detected in the human intestine [ 48 ] and some exhibit important hydrolytic activities (e.g., xylanase, β-xylosidase β-galactosidase, α- and β-glucosidase, α-amylase, pectin methyl-esterase, pectate lyase, N-acetyl-β-glucosaminidase) [ 49 ]. Lower amounts of Lachnospiraceae were previously reported in a subject suffering from UC [ 50 ], however, Vacca et al [ 51 ] pointed out the increased abundance of Lachnospiraceae in the intestinal lumen of subjects with different diseases, thus indicating the possible controversial role of this taxon. Nevertheless, several genera are known for their positive effect on health, especially butyrate-producing strains of Butyrivibrio , Roseburia , Anaerostipes , or Coprococcus [ 52 ].…”
Section: Discussionmentioning
confidence: 92%
“…Many Lachnospiraceae members have been detected in the human intestine [ 48 ] and some exhibit important hydrolytic activities (e.g., xylanase, β-xylosidase β-galactosidase, α- and β-glucosidase, α-amylase, pectin methyl-esterase, pectate lyase, N-acetyl-β-glucosaminidase) [ 49 ]. Lower amounts of Lachnospiraceae were previously reported in a subject suffering from UC [ 50 ], however, Vacca et al [ 51 ] pointed out the increased abundance of Lachnospiraceae in the intestinal lumen of subjects with different diseases, thus indicating the possible controversial role of this taxon. Nevertheless, several genera are known for their positive effect on health, especially butyrate-producing strains of Butyrivibrio , Roseburia , Anaerostipes , or Coprococcus [ 52 ].…”
Section: Discussionmentioning
confidence: 92%
“…These findings are also in agreement with previous reports showing negative correlations of the genera Ruminococcaceae NK4A214 and Lachnospiraceae NK4A136 groups with HFD consumption [ 79 , 80 ]. One of the vital functions of Ruminococcaceae and Lachnospiraceae produced short-chain fatty acids (SCFA), such as butyric acid and acetic acid [ 81 , 82 ]. SCFA plays an important role in maintaining a healthy condition because they may minimize the risk of many diseases, including type 2 diabetes and obesity [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to be creatinine [ 63 ]. Other studies have also shown that intestinal dysbiosis occurs in CKD and can actively contribute to the progression of renal failure [ 64 ]. The main characteristic of CKD dysbiosis is an increase in Proteobacteria [ 65 ], but an increase in Lachnospiraceae has also been observed [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%